Parenting support from grandparents and work-family conflict among working mothers: The mediating role of parenting stress - Ni Putu Adelia Kesumaningsari; Faith Joanna Hartoyo; Yuan Yovita Setiawan (Universitas Mercu Buana Yogyakarta, 2025)
The growing participation of mothers in the workforce in Indonesia is increasing the demand for external support in managing both family and occupational responsibilities. Grandparental participation in childcare represents a potential form of support even though the positive effects can be mediated rather than direct. Therefore, this study aims to investigate the role of parenting stress as a mediator in the relationship between grandparental support and work-family conflict (WFC) among working mothers. The adoption of the quantitative method led to the collection of data specifically using online questionnaires. The samples consisted of 174 working mothers aged 21–50 years across Indonesia who had children aged 0–12 years and received a minimum of 12 hours of childcare support per week from grandparents selected through a purposive sampling method. The questionnaires were filled out through the modified Parenting Support Scale, the WFC Scale, and the Parental Stress Scale. The data were analyzed using PROCESS Macro v4.3 by Hayes and the results showed that the parenting support from grandparents significantly reduced parenting stress and subsequently lowered WFC. Parenting stress also fully mediated the relationship between the support from grandparents and WFC. These results emphasized the importance of extended family support particularly from grandparents in mitigating psychological burdens and facilitating work-life integration among working mothers in Indonesia. Keywords: Grandparents; parenting stress; parenting support; work–family conflict; working mothers